Karl Heinzinger and computer modelling of water and aqueous solutions - A. Trokhymchuk; Ph. Bopp; E. Spohr; M. Holovko (Condensed Matter Physics, 2023)
This brief essay commemorates Karl Heinzinger, one of the pioneers in the field of computer modelling of fluid systems, particularly of water and aqueous electrolyte solutions in the bulk phase and near interfaces. Karl Heinzinger died peacefully on January 14, 2023, after a short illness. We express our deepest condolences to his family, colleagues, and friends.